Implementation of the Jigsaw Learning Model with the Assistance of E-Books and Audiovisual Media to Improve Sports Massage Learning Outcomes - Dian Pujianto; Bayu Insanistyo; Mas'ullah Andriyani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Learning outcomes obtained by students is one of the factors that determine success in the learning process. However, it is very unfortunate that not all students get optimal learning results. This classroom action research aims to analyze the increase in student learning outcomes through the application of the jigsaw learning model in sports massage lectures. Implementation of the action consists of two cycles with each cycle consisting of 4 meetings. The research subjects consisted of 39 physical education students. Collecting research data using written tests and skills tests. Data analysis was performed using a quantitative description. The results of the study revealed that the average value of cycle 1 learning outcomes was 63.85 and classical completeness was 62.23%. While the average value of learning outcomes in cycle 2 is 80.08 and classical completeness is 87.18%. Based on the results of this study it was concluded that the application of the jigsaw learning model assisted by e-books and audiovisual media proved effective in improving student learning outcomes in sports massage lectures.